Land aggregation at the river reserve area along Sungai Perlis using GIS approach / Nurfarhani Ahmad Faisal - Ahmad Faisal, Nurfarhani (2022)
The aggregation of land is a perpetual problem that exists even now in many places of the country. Many developing nations such as Malaysia lack data on the types and area of land aggregation at river reserve areas. Therefore, this research aims were to analyze land aggregation at river reserve area along Sungai Perlis using GIS approach. In order to achieve this study, three objectives were established which were i) to determine the land aggregation types at river reserve area in Sungai Perlis ii) to identify total area of land aggregation at Sungai Perlis reserve area. To fulfil the objectives, ArcGIS is used to digitize the land aggregation at river reserve areas. This study conducted by digitizing the land aggregation area and used classification technique to classify the land aggregation types. As a result, the land aggregation map at the river reserve area of Sungai Perlis will be generated to identified types and total area of land aggregation. This research may be useful and helpful for local authorities monitoring the total area and locality of land aggregation in Sungai Perlis reserve area.